Standards of Proof and Legal Dilemmas in the Identification of the Remains of Victims of Forced Disappearance. A Look from the Chilean Experience - Accatino, Daniela (2023)
The challenge of the search for victims of enforced disappearance usually includes the recovery of the identity of the remains that are found. This paper highlights the legal dimension of identification and its quality as a decision about the proof of a fact, which can be analyzed with the conceptual tools of the theory of legal evidence. On that basis, it analyzes the question about the applicable standard of proof considering the recent Chilean experience, which shows how positive DNA evidence has tended to consolidate as a sort of golden standard, exclusive and excluding, for the identification of human remains in the case of enforced disappearances. However, that standard of certainty will be often difficult to meet because of deterioration of DNA in the remains samples obtained, because of the scarcity of samples given the practice of massive clandestine exhumations or because of a lack of relatives’ samples for comparison. The paper explores the questions that then open up, regarding both the possibility that other forensic evidence may be acceptable as sufficient and the treatment of the unidentified remains.